Seasonal Assessment of Heavy Metal Pollution in Street Dust of Nicosia City in North Cyprus - Kidak, Rana (European Journal of Sustainable Development, 2017)
Heavy metals concentration is increasingly becoming health concern in the world, particularly on street dust of urban cities with high density traffic. Road dust samples were analyzed for determination of concentrations of the environmentally sensitive elements As, Co, Cr, Cu, Ni, Pb, and Zn in fraction of dust smaller than 100 ?m. The dust particles were collected during winter and summer seasons from highways, residential and industrial areas representing different activities across the Nicosia city. The dust samples were measured for their contamination levels and particles size distribution. The assessment of pollution was based on single pollution indices, integrated pollution indices and Pearson moment correlation in order to determine their possible source, spatial distribution and seasonal variations. Single Indices include Contamination Factor (Cf), Index of Geo-accumulation (Igeo) and the integrated indices include degree of contamination (Dc) and Pollution Load Index (PLI). The general pattern of occurrence of heavy metals follows the order of Cr>Zn>Cu>Ni>Pb>Co>As. The highest levels of Cr, Zn and Cu were found in the high traffic density area, and strong positive correlations were found between these metals, implying that automobile exhausts are the dominant source of these metals. Keywords: Heavy metals, pollution indices, particles size distribution, seasonal variation.